Real-time X-ray microscopy study of electromigration in microelectronic solder joints. (15th March 2016) - Ho, Cheng-En; Yang, Cheng-Hsien; Lee, Pei-Tzu; Chen, Chih-Tsung
Abstract: Electromigration (EM) in microelectronic solder joints was investigated via transmission X-ray microscopy (TXM) in conjunction with three-dimensional computed microtomography (3D μ-CT). This nondestructive analysis provided visualization of the EM dynamics in the encapsulated solder joints and showed the linear dependence of the Cu pad depletion on the current stressing time. Quantitative analysis of the interstitial Cu diffusion in β-Sn based on Huntington's EM theory offered rationalization of this EM-induced degradation mechanism. Graphical abstract: